Does Islamic banking matter for economic growth in Bangladesh? - Abduh, Muhamad; Chowdhury, Nazreen T. (Islami Bank Training and Research Academy, 2012)
Islamic banking started three decades ago in Bangladesh and was expected to have a significant relationship and contribution towards the economic growth of the country. This study aims to investigate the long run and dynamic relationship between Islamic banking development and economic growth in the case of Bangladesh. The quarterly time-series data of economic growth, total financing and total deposit of Islamic banking from Q1:2004 to Q2:2011 are used in this study. Using cointegration and Granger’s causality method, Islamic bank financing is found to have a positive and significant relationship with economic growth both in the long and short run. It implies that the development of Islamic banking is one of the policies, which should be considered by the government to improve their income.